PENGARUH DURASI DAN CONVEXITY TERHADAP HARGA OBLIGASI PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018 - 2021 - Debataraja, Mega Silvia; Silalahi, Donalson (KUKIMA : Kumpulan Karya Ilmiah Manajemen, 2022)
This study aims to determine and explain the effect of duration and convexity on bond prices. To achieve this purpose, research was conducted on banking companies listed on the Indonesia Stock Exchange in 2018 - 2021. The data used in this study is secondary data. By using purposive sampling as a sampling method, the number of samples observed was 15 companies and the analytical tool used was multiple linear regression. The results show that duration has a positive and significant effect on bond prices, convexity has a positive and significant effect on bond prices. Simultaneously, variations in duration and convexity can explain variations in bond prices by 39.9 percent